MODEL PEMBELAJARAN KOLABORATIF UNTUK MENGATASI KETIDAKSEIMBANGAN JUMLAH SISWA DAN PENGAJAR DI TPQ - manik, lia; Istikhomah (Journal of Islamic Science Community, 2024)
Abstract TPQ Raudlotul Jannah in Dukuh Tamansari, Carangrejo Village, Ponorogo Regency, is a religious education center that strengthens understanding of religion and the Koran amidst the natural beauty of the countryside. Despite being faced with a lack of teachers who mastered Ottoman methods, TPQ succeeded in overcoming these challenges through a collaborative learning approach involving teachers, students, parents and local communities. Support from all relevant parties has created an inclusive and effective learning environment, ensuring equal access for all students. The implementation of this collaborative learning model has improved the quality of Al-Qur'an learning at TPQ, helped students prepare for the munaqosah exam, and created a dynamic and sustainable learning environment.